Jalapeño and Other Hot Pepper Varieties for Florida - Monica Ozores-Hampton; Gene McAvoy (EDIS)
The jalapeño is derived from the Capsicum genus of the family Solanaceae. Jalapeños are members of a diverse group, which also include ancho poblano, cayenne, serrano, Anaheim, banana, Asian, habanero, and Hungarian wax peppers. Hot peppers are classified by their heat and shape. The heat of the pepper comes from the chemical compound capsaicin, which is measured by the Scoville scale. This 8-page fact sheet is a guide of jalapeño and other hot pepper varieties used in Florida was written by Monica Ozores-Hampton and Gene McAvoy, and published by the UF Department of Horticultural Sciences, October 2014.